Electrochemical charging of the single‐layer graphene membrane. Issue 12 (28th June 2016) - Komínková, Zuzana; Kalbáč, Martin
Abstract : In situ Raman spectroelectrochemistry has been applied to study chemical vapor‐deposition‐grown single‐layer graphene membrane on a patterned SiO2 /Si substrate. The SiO2 /Si substrate is known to dope graphene, thus the substrate can significantly influence the properties of the graphene during electrochemical charging. We analyzed the change of the Raman intensity of the G mode as a function of electrode potential for a single‐layer graphene membrane and we compared the results to those obtained for the same graphene sample on a substrate. Because of the elimination of the influence of a supporting substrate we have been able to achieve more efficient doping of graphene by applied electrode potentials.